Navigating medications: a prospective study on drug use in rheumatoid arthritis management - Kumar, Ashok; Khan, Mohammad Nadeem (International Journal of Basic & Clinical Pharmacology, 2025)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease-causing joint inflammation, pain, and potential joint damage. Effective management requires a combination of pharmacologic treatments to reduce disease activity and improve patient outcomes. Methods: This prospective study investigated drug utilization patterns, medication adherence, and their impact on RA management. Data were collected over one year from 510 RA patients visiting the orthopaedic department at Raichur Institute of Medical Sciences. Demographic details, clinical characteristics, medication regimens, adherence levels, and adverse drug reactions were recorded. Results: Female patients, primarily aged 51-65 years, were predominantly affected by RA. Non-steroidal anti-inflammatory drugs (NSAIDs) were the most commonly prescribed medications, with oral administration being preferred. Family history and older age were significant risk factors. Disease-modifying anti-rheumatic drugs (DMARDs), especially in combination, were preferred for managing RA. NSAID usage led to adverse effects like gastric discomfort, underscoring the need for careful monitoring. Conclusions: This study highlights the importance of early detection, personalized treatment strategies, and the need for further research into novel therapies. It offers valuable insights into drug utilization and medication adherence, with implications for improving RA management and patient outcomes.